Serve & solve : enhancing server skills through interactive learning - Abdullah, Hasniza; Tarmazi, Siti Anis Adilah; Syed Hamzah, Syarifah Atifah; Saiful, Syaidatul Salmah Nurbalqis (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
Serve & Solve is an innovative app designed to revolutionize hospitality training through interactive and gamified learning. It addresses the limitations of traditional training methods by simulating real-world restaurant scenarios, enabling users to practice critical skills such as communication, problem-solving, and customer service in a dynamic environment. The app was developed to bridge the gap between theoretical knowledge and practical application, offering a hands-on, engaging, and accessible solution for students and professionals in the hospitality sector. Key features of Serve & Solve include role-playing exercises, real-time feedback, gamified rewards to boost engagement, and integrated customer psychology insights. These unique elements ensure comprehensive learning while fostering confidence and adaptability. The app’s design prioritizes accessibility, making it available on both web and mobile platforms to cater to a broad user base. Serve & Solve socio-economic impact is profound, preparing a skilled workforce ready to meet the demands of a competitive hospitality industry. By enhancing customer service standards, it contributes to improved workplace efficiency and customer satisfaction. The app’s commercialization potential is vast, targeting hospitality schools, training programs, and businesses through subscription models and corporate partnerships. Serve & Solve stands out as a forward-thinking solution that nurtures innovation, professionalism, and entrepreneurship within the hospitality community and beyond.